175: Procedural Skills in Pediatric Residency and in Practice. Issue 6 (1st June 2014) - Kay, S; Rayar, M; Hunter, A; Valani, R
Abstract: BACKGROUND: The Royal College of Physician and Surgeon of Canada mandates that all pediatric trainees gain expertise in specific procedural skills prior to completing their training. The current landscape of medical education, however, may not provide residents with enough opportunity to observe and perform such skills. The reason for this change is multifactorial; with factors such as reduction in learners' working hours or a movement towards more non-invasive treatments. The cumulative effect could be that residents fail to achieve the competency required in essential procedures by the end of their training. OBJECTIVES: To determine the frequency and level of comfort of pediatric residents in performing procedural cited as essential to the practice of general pediatrics by the Royal College of Physicians and Surgeons of Canada. To examine if there is any perceived difference in the importance of competency in each procedural skill between residents and practicing general pediatricians. DESIGN/METHODS: This prospective survey was undertaken at a single academic institution. Residents and general pediatricians were surveyed on how often they performed procedures listed by the Royal College of Physicians of Canada training objectives. Participants were also asked to rate their confidence level in performing each skill, along with their perception of which skills were necessary for pediatrics practice. RESULTS: Thirty seven participants completed the survey (22 residents, 15 staff). 14 residents were in their first two years of training. All staff physicians had community practices, >90% also had academic appointments. 100% of residents and practitioners identified neonatal and pediatric resuscitation skills as essential to practice though used this skill set <5 times in the last year. Competence in all other non-resuscitation procedures were rated as either useful or important, but not essential to general pediatrics. The emphasis placed on a skill was not predictably related to the frequency they were performed. Residents uniformly described less confidence in performing all procedures than attending physicians. CONCLUSIONS: This study shows that despite limited training and exposure to a skill, residents are able to distinguish which procedural skills are important to the practice of general pediatrics.